Studi Literatur Tingkat Keanekaragaman Gastropoda sebagai Sumber Belajar Biologi SMA Kelas X pada Materi Keanekaragaman Hayati - Ayu Prabaningrum; Yahya Hanafi; Destri Ratna Ma’rifah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
Learning resources are one of the important things in improving the learning process. One of the material for high school class X that requires learning resources that come from the environment is the material on biodiversity. Learning practices in schools generally still use conventional learning resources, and have not used the environment as a learning resource. The purpose of the study was to analyze the requirements of biology learning resources based on research results from literature studies. This research is a literature study research, which is looking for relevant references to research on the Literature Study of Gastropod Diversity Level as a Biology Learning Source for Class X High School on Biodiversity Material. Data analysis used is descriptive qualitative analysis with narrative review method. This study uses 10 scientific articles on the diversity of Gastropods. The results of the study through a literature study found that the Gastropod diversity index had a diversity index of high category H' = 3.0468 and 3.0075. Medium category gastropod diversity index H' = 1.9915; 1,695; 1.5858-1.18742; 2,412; 2.232; 2,059; 1.4786-1.9382; 1,226; 1,251; 2,236; 1.22; and 1.39. Low category gastropod diversity index H' = 0.296; 0.180; 0.972; 0.113; and 0.668. The results of the analysis of the potential requirements for learning resources that have been carried out show that the results of research on gastropod diversity meet the requirements as a source for learning biology in high school class X on the subject of biodiversity.